Dual Proportional Integral Controller of Two-Area Load Frequency Control Based Gravitational Search Algorithm - M. Elsisi; M. Soliman; M. A. S. Aboelela; W. Mansour (Institute of Advanced Engineering and Science, 2015)
Gravitational Search Algorithm (GSA) has recently been explored to develop a novel algorithm for distributed optimization and control. This paper proposes a dual Proportional Integral (PI) controller of Load Frequency Control (LFC) based GSA to enhance the damping of oscillations in a two-area power system. A two-area non-reheat thermal system is considered to be equipped with dual PI controller. GSA is utilized to search for optimal controller parameters by minimizing a time-domain based objective function. The performance of the proposed controller has been evaluated with the performance of the conventional PI controller, and PI controller tuned by GSA in order to demonstrate the superior efficiency of the proposed dual PI controller tuned by GSA. Simulation results emphasis on the better performance of the optimized dual PI controller based on GSA in compare to optimized PI controller based on GSA and conventional one over wide range of operating conditions, and system parameters variations. DOI: http://dx.doi.org/10.11591/telkomnika.v15i1.8093